2018
DOI: 10.30871/jaba.v1i2.616
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Financial Distress, Real Earnings Management Dan Corporate Governance Terhadap Tax Aggressiveness

Abstract: This study is aimed to examine the effect of financial distress, real earnings management, and corporate governanceon tax aggressiveness. Using samples from manufacturing companies listed on the Indonesia Stock Exchange in the period 2011 to 2015, the data will be examined with fixed effect approach method. The results of this study indicate that financial distress does not affect on tax aggressiveness. While from real earnings management variables, only through manipulation of sales as which affects positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
2
47

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(70 citation statements)
references
References 3 publications
(3 reference statements)
2
19
2
47
Order By: Relevance
“…Companies with higher institutional ownership tend to lower tax aggressiveness than companies with low institutional ownership (Badertscher et al, 2009). The results of this study are consistent with the research of Nugroho & Firmansyah (2017), Hanna & Haryanto (2016), Cahyono et al, (2016), Fadli (2016), Embree (2012), Khurana & Moser (2009) that found an effect of institutional ownership on tax aggressiveness.…”
Section: The Effect Of Institutional Ownership On Tax Aggressivenesssupporting
confidence: 92%
See 3 more Smart Citations
“…Companies with higher institutional ownership tend to lower tax aggressiveness than companies with low institutional ownership (Badertscher et al, 2009). The results of this study are consistent with the research of Nugroho & Firmansyah (2017), Hanna & Haryanto (2016), Cahyono et al, (2016), Fadli (2016), Embree (2012), Khurana & Moser (2009) that found an effect of institutional ownership on tax aggressiveness.…”
Section: The Effect Of Institutional Ownership On Tax Aggressivenesssupporting
confidence: 92%
“…the management tends to manipulate profit in order to avoid government regulation, one of which is to avoid corporate income tax. The results of this study are consistent with Nugroho & Firmansyah (2017), Prawira (2017), Wulansari (2015), Pranoto & Widagdo (2015), Fadli (2013), Suyanto & Supramono (2012) which shows that earnings management has an effect on tax aggressiveness.…”
Section: The Effect Of Earnings Management On Tax Aggressivenesssupporting
confidence: 89%
See 2 more Smart Citations
“…Companies that are in financial distress increase tax aggressiveness to generate additional cash outflows (Richardson, Lanis, & Taylor, 2014). Nugroho and Firmansyah (2017) in their research gave a real example when there is an economic crisis in Indonesia found that many companies experience financial distress or high financial distress so that they are no longer able to maintain the company's survival due to continuous losses, have very large debts and lack of cash to pay off the debt. In the condition of financial distress, companies are required to save capital or meet the minimum capital needed by the company, so that the company is still able to maintain credit ratings, meet the requirements of debt agreements, or continue as a going concern company (Richardson, Taylor, and Lanis, 2015).…”
Section: Introductionmentioning
confidence: 99%